Trend of Sexual Offences in Pakistan (Medical Forum Monthly, 2020)
Objective: To Study Trend of Sexual Offences in Pakistan.Study Design: Retrospective StudyPlace and Duration of Study: This study was conducted at the Departments of Forensic Medicine, FMC, Abbatabad, SMC, Sialkot, RMDC, Lahore and FJMU, Lahore from Feb 2018 to Jan 2020.Materials and Methods: Two Hundred and sixty-three Victims of sexual offences were included in this study. Th e performa was designed to record demographic data. Injuries inflicted during sexual offence, Swab positive and negative were recorded. The history & examination was also recorded in the performa. The permission of Ethical Committee was also considered before collecting the data and get publish Medical Journal. The written informed consent was also taken before collecting the data. The results were analyzed by SPSS version 10.Results: The incidence of sexual offences was maximum in age group 11-15years 7(21.21%) and minimum in age group 51-70years 1(3.03%) in male and in female incidence was maximum in age group 26-30years 37(16.15%) and minimum in age group 71 & above years 09(3.93%). The incidence of sexual offences was maximum in Lower class o population 135(51.33%) and minimum in high gentry 27(10.26%). The incidence of sexual offences was maximum in rural population 201(74.42%) as compared to urban population 62(23.57%) as most of the people live in rural area. There was 173(65.77%) victims who had swab positive and 90(34.22%) swab negative. There was maximum incidence of injuries of genital area & genital tract 76(28.89%) and minimum incidence of injuries chest & abdomen 27(10.26%).Conclusion: Women reaching the at risk age should be educated regarding the signal warning of danger for such a prevalence and how best to respond to such a situation. Survivors and the closely associated people should be educated to rep on such an incident immediately and get the victim examined so that proper evidence can take place and evidence collected. Facilities for seminal fluid grouping and Deoxy Ribo Nuclic Acid analysis should be developed to help in identifying the illegal. Finally,